2018
DOI: 10.1002/jsfa.9064
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal processing towards lipid oxidation and non‐enzymatic browning reactions of Antarctic krill (Euphausia superba) meal

Abstract: The lipid oxidation level of Antarctic krill increased after drying, owing to prolonged heating under the severe conditions. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…18 Liu et al studied the lipid oxidation of krill powder during thermal processing using lipidomics. 19 In the past decade, ambient ionization MS had been an increasingly attractive field for food researchers to achieve the benefits of traditional MS with high-throughput, real-time, and in situ analysis, which is driven by the ability to conduct the analysis of a sample under normal atmospheric conditions without a preparative step, chromatographic separation, and limited dead volume of MS inlet. 20 Rapid evaporative ionization MS (REIMS) is a state-of-the-art ambient ionization MS technique, which yields highly specific lipid phenotypes of various biological tissue types and develops a samplepreparation-free, real-time, and lipidomics-based microbial identification system.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Liu et al studied the lipid oxidation of krill powder during thermal processing using lipidomics. 19 In the past decade, ambient ionization MS had been an increasingly attractive field for food researchers to achieve the benefits of traditional MS with high-throughput, real-time, and in situ analysis, which is driven by the ability to conduct the analysis of a sample under normal atmospheric conditions without a preparative step, chromatographic separation, and limited dead volume of MS inlet. 20 Rapid evaporative ionization MS (REIMS) is a state-of-the-art ambient ionization MS technique, which yields highly specific lipid phenotypes of various biological tissue types and develops a samplepreparation-free, real-time, and lipidomics-based microbial identification system.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Many research studies have demonstrated that the mass spectrometry (MS)-based lipidomics method has been successfully used to evaluate food raw materials, optimize food processing methods, detect food adulteration, and so forth. , Zhang et al analyzed the difference in lipid species and nutritional values between freshwater and marine fish species based on specific lipidomic phenotypes . Liu et al studied the lipid oxidation of krill powder during thermal processing using lipidomics . In the past decade, ambient ionization MS had been an increasingly attractive field for food researchers to achieve the benefits of traditional MS with high-throughput, real-time, and in situ analysis, which is driven by the ability to conduct the analysis of a sample under normal atmospheric conditions without a preparative step, chromatographic separation, and limited dead volume of MS inlet .…”
Section: Introductionmentioning
confidence: 99%
“…The POV was determined using a method adapted from Liu et al . (2018) with a few modifications. Briefly, the sample containing 20 mg krill oil was dissolved in chloroform/methanol (7:3, v/v), followed by the addition of 50 µL of 20 mmol/L ferrous chloride solution in 0.2 mol/L HCl.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that steaming or boiling process improves the nutritive values of tilapia by increasing the content of eicosapentaenoic acid (EPA) and DHA, two officially recommended fatty acids. To better explain the decrease in nutritional value caused by lipid oxidation in the processing of aquatic products, chemical reactions and oxidation of lipids (especially EPA and DHA) during thermal processing of krill powder were studied at the molecular level using lipidomics (Liu et al., 2018). These studies will help the food industry to produce high‐quality products, ensure food quality and safety, and improve consumer acceptance.…”
Section: Application Of Ms‐based Lipidomics In Food Sciencementioning
confidence: 99%